Month of the Year Effect pada Pasar Obligasi di Indonesia - Robiyanto Robiyanto (Jurnal Ekonomi dan Bisnis, 2017)
This study examines the month-of-the-year effect on the bond returns in Indonesia. I use the monthly closing price index (Indonesia Bond Indexes / INDOBeX) data for the periods of July 2003-July 2017 from Bloomberg. I then run the Generalize Autoregressive Conditional Heteroscedasticity (GARCH) analysis technique to analyze the data because the residuals exhibit a significant pattern of Autoregressive Conditional Heteroscedasticity (ARCH). The results show that only the month of July has a significantly positive effect on the bond returns; indicating that there is the month-of-the-year effect in the Indonesian bond market. Further, these also imply that the Indonesian bond market does not exhibit a random walk pattern and consequently they are inefficient in the weak form.